Starfish - Bowman, Akemi Dawn (Simon Pulse, 2017)
Kiko Himura yearns to escape the toxic relationship with her mother by getting into her dream art school, but when things do not work out as she hoped Kiko jumps at the opportunity to tour art schools with her childhood friend, learning life-changing truths about herself and her past along the way.